2023
DOI: 10.1177/09603271231198624
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of topiramate and spirulina against doxorubicin-induced cardiotoxicity in rats

Radwa M Elmorsi,
Amira A El Saadany,
Ahmed M Kabel
et al.

Abstract: Doxorubicin (DOX) is a widely used chemotherapy drug that can cause significant cardiotoxicity, limiting its clinical application. This study aimed to investigate the potential protective effects of topiramate (TPM) and spirulina (SP), either alone or in combination, in preventing DOX-induced cardiotoxicity. Adult Sprague Dawley rats were divided into five groups, including a normal control group and groups receiving DOX alone, DOX with TPM, DOX with SP, or DOX with a combination of TPM and SP. Cardiotoxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Parallel to these results Arozal et al (2010) showed that TEL has antiapoptotic properties against daunorubicin-induced cardiotoxicity, whereas TEL significantly decreases the number of TUNEL-positive nuclei and expression of activated caspase-7 in addition to upregulation of Bcl2 expression. Another experimental study by Elmorsi et al (2023) showed that Sp monotherapy downregulated caspase-3 immunoreactivity in doxorubicin-induced cardiotoxicity. A study by Sinanoglu et al (2012) reported that Sp supplementation (1000 mg/kg bw/day) for 7 days may be able to downregulate apoptosis in the kidneys of rats intoxicated with Cyclo through downregulation of caspase-3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel to these results Arozal et al (2010) showed that TEL has antiapoptotic properties against daunorubicin-induced cardiotoxicity, whereas TEL significantly decreases the number of TUNEL-positive nuclei and expression of activated caspase-7 in addition to upregulation of Bcl2 expression. Another experimental study by Elmorsi et al (2023) showed that Sp monotherapy downregulated caspase-3 immunoreactivity in doxorubicin-induced cardiotoxicity. A study by Sinanoglu et al (2012) reported that Sp supplementation (1000 mg/kg bw/day) for 7 days may be able to downregulate apoptosis in the kidneys of rats intoxicated with Cyclo through downregulation of caspase-3 expression.…”
Section: Discussionmentioning
confidence: 99%